SPEED AND STRENGTH QUALITIES OF WRESTLERS 16-18 YEARS OLD DEVELOPMENT SERVICES (International Scientific Journal Alfraganus, 2024)
This article discusses the development of fast-strength qualities of wrestlers aged 16-18 years,their special fast-strength qualities, methods of their development, the development of physicalactivity in training sessions, and research of the training process. according to the way theydevelop.
Keywords: wrestling, speed-strength training, quality, methodology, development, training, anthropometric measurements, medical control, exposure time, speed abilities, load, training.